MONITORING OF IC ENCAPSULATION PROCESS - V. A. Saladukha; V. S. Turtsevitch; J. A. Solovjov; I. I. Rubtsevitch; A. F. Kerentsev; A. A. Dovzhenko; I. V. Chirko (Приборы и методы измерений)
High reliability of ASICs in metal-ceramic packages at the stage of manufacturing is achieved as a result of minimization of moisture content inside the package and due to continuous measurements of parameters of the encapsulation environment. It is shown that the use of instruments for checking the conditions of contact welding and the instruments for complex measurements of parameters of the ambient environment of the encapsulation system has allowed to provide a continuous monitoring of the process parameters: welding current, temperature, dew point and relative humidity of an inert ambient environment. As the result of seam welding, increase of yield fitted in hermeticity over 99,0 % and decrease the moisture content inside the IC package to vol. 0,01–0,2 % has been reached.